Two Functional Variants of AP-1 Complexes Composed of either γ2 or γ1 Subunits Are Independently Required for Major Histocompatibility Complex Class I Downregulation by HIV-1 Nef - Tavares, Lucas A.; de Carvalho, Julianne V.; Costa, Cristina S.; Silveira, Roberta M.; de Carvalho, Andreia N.; Donadi, Eduardo A.; daSilva, Luis L. P. (Journal of virology, 2020)
HIV-1 Nef mediates evasion of the host immune system by inhibiting MHC-I surface presentation of viral antigens. To achieve this goal, Nef modifies the intracellular trafficking of MHC-I molecules in several ways. Despite being the subject of intense study, the molecular details underlying these modifications are not yet fully understood. Adaptor protein 1 (AP-1) plays an essential role in the Nef-mediated downregulation of MHC-I molecules such as HLA-A in different cell types. However, AP-1 has two functionally distinct variants composed of either γ1 or γ2 subunit isoforms. Because previous studies on the role of AP-1 in MHC-I downregulation by Nef focused on AP-1γ1, an important open question is the participation of AP-1γ2 in this process. Here, we show that AP-1γ2 is also essential for Nef-mediated depletion of surface HLA-A molecules in T cells. Our results indicate that Nef hijacks AP-1γ2 to modify HLA-A intracellular transport, redirecting these proteins to lysosomes for degradation. The HIV-1 accessory protein Nef downregulates the cell surface expression of major histocompatibility complex class I (MHC-I) molecules to facilitate virus spreading. The Nef-induced downregulation of MHC-I molecules such as HLA-A requires the clathrin adaptor protein 1 (AP-1) complex. The cooperative interaction of Nef, AP-1, and the cytosolic tail (CT) of HLA-A leads to a redirection of HLA-A targeting from the trans -Golgi network (TGN) to lysosomes for degradation. Although the γ-adaptin subunit of AP-1 has two distinct isoforms (γ1 and γ2), which may form two AP-1 complex variants, so far, only the importance of AP-1γ1 in MHC-I downregulation by Nef has been investigated. Here, we report that the AP-1γ2 isoform also participates in this process. We found that AP-1γ2 forms a complex with Nef and HLA-A2_CT and that this interaction depends on the Y 320 residue in HLA-A2_CT and Nef expression. Moreover, Nef targets AP-1γ1 and AP-1γ2 to different compartments in T cells, and the depletion of either AP-1 variant impairs the Nef-mediated reduction of total endogenous HLA-A levels and rescues HLA-A levels on the cell surface. Finally, immunofluorescence and immunoelectron microscopy analyses reveal that the depletion of γ2 in T cells compromises both the Nef-mediated retention of HLA-A molecules in the TGN and targeting to multivesicular bodies/late endosomes. Altogether, these results show that in addition to AP-1γ1, Nef also requires the AP-1γ2 variant for efficient MHC-I downregulation. IMPORTANCE HIV-1 Nef mediates evasion of the host immune system by inhibiting MHC-I surface presentation of viral antigens. To achieve this goal, Nef modifies the intracellular trafficking of MHC-I molecules in several ways. Despite being the subject of intense study, the molecular details underlying these modifications are not yet fully understood. Adaptor protein 1 (AP-1) plays an essential role in the Nef-mediated downregulation of MHC-I molecules such as HLA-A in different cell types. However, AP-1 has two functionally distinct variants composed of either γ1 or γ2 subunit isoforms. Because previous studies on the role of AP-1 in MHC-I downregulation by Nef focused on AP-1γ1, an important open question is the participation of AP-1γ2 in this process. Here, we show that AP-1γ2 is also essential for Nef-mediated depletion of surface HLA-A molecules in T cells. Our results indicate that Nef hijacks AP-1γ2 to modify HLA-A intracellular transport, redirecting these proteins to lysosomes for degradation.